Amniotic Fluid. Origin, volume, circulation. - Cervantes Begazo, René (2015)
The amniotic fluid once considered an inert, static mass surrounding the fetus, has become a rich source of clinical data which may be decisive in conducting pregnancy. Either through examination of their constituents, after obtaining the fluid by transabdominal amniocentesis, or by observing its color and appearance through the amnioscopy, or as a vehicle for the introduction of diagnostic or therapeutic substances, the fact is that now the amniotic fluid is widely used in clinical diagnostic and therapeutic procedures obstetric field, necessitating adequate knowledge of their physiological characteristics to the correct interpretation of the data.